Lived Experiences of Filipino Nurses Working in the Medical and Surgical Departments of Darlington Memorial Hospital, United Kingdom - Jezalyn O. Vargas; Jane M. Tagum-Briones; Cyril B. Romero; Carlen Lagyap De Villa (The Indonesian Institute of Science and Technology Research, 2026)
This study explored the lived experiences of twenty-six (26) Filipino nurses working in the medical and surgical departments of Darlington Memorial Hospital (DMH), United Kingdom. Using a descriptive research design and a self-developed, expert-validated survey, the study examined their cultural adaptation, workplace environment, and support systems. It also analyzed the relationship between their demographic profiles (age, sex, civil status, length of service, and department) and these experiences. The results showed that most respondents were young (31–40 years old), female, married, and relatively new to DMH (1–3 years of service), with many working in the Operating Room. Overall, participants expressed positive experiences (grand mean = 3.16), with the workplace environment receiving the highest rating (mean = 3.29,